Novel nanogel carrier cross-linked through ultraviolet light as well as preparation method and application of novel nanogel carrier
By cross-linking the nanogel carrier with ultraviolet light, hyaluronic acid and cytochrome C, combined with the cystamine group disulfide bond, the problem of poor targeted release of protein therapy in cancer treatment is solved, Achieve more efficient tumor targeting and release effects.
Patent Information
- Application Number
- CN202411339959.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-24
AI Technical Summary
The existing protein therapy has problems such as poor targeted release, short inactivation time and poor membrane permeability in cancer treatment, resulting in unsatisfactory treatment results.
UV cross-linked nanogel carrier, grafting diethylenetriamine and methoxypolyethylene glycol amino in nanogels, using hyaluronic acid as the backbone and cytochrome C as the carrier, binding to cystamine groups Disulfide bonds achieve responsive release to the tumor microenvironment.
It improves the targeting and release efficiency of drugs, extends the circulation time in the blood, enhances the phagocytosis ability of tumor cells, and rapidly decreases and releases drugs in the tumor microenvironment, improving the therapeutic effect.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nano-biomedicine, and includes the construction of a tumor microenvironment-responsive nano-gel carrier and the delivery of proteins in vivo. Background Art
[0002] Cancer is the main enemy of human health in my country and even in the world, and its incidence is also increasing. The commonly used cancer treatment methods cannot provide satisfactory treatment effects, and have defects such as low specificity, strong toxic side effects, and high recurrence rate. Early cancer is difficult to detect, and cancer cells are easy to metastasize and spread through lymphatic vessels and other pathways, resulting in high cancer cure. The current clinical cancer treatment methods are surgery, radiotherapy and chemotherapy. However, surgical treatment has the disadvantages of high risk, large trauma area and easy recurrence; radiotherapy and chemotherapy will damage the body's normal cells while killing cancer cells, resulting in damage to normal physiological functions. Therefore, humans urgently need to develop new cancer diagnosis and treatment strategies to overcome this medical problem.
[0003] In recent years, the increasing number of clinically translated protein therapeutics for the treatment of many human diseases, including malignancies and cardiovascular diseases, has attracted great attention. Such therapeutic proteins are generally safe and non-toxic, with good specificity and excellent anti-tumor efficacy. However, they also have some disadvantages, such as poor in vitro and in vivo stability, short blood half-life, enzymatic degradation, non-targeted cytotoxicity, and subcellular permeability. In order to improve the therapeutic efficiency of apoptotic proteins against cancer, from polymer micelles to various nanocarriers, polymers, liposomes, nanogels, to hydrogels. Design and exploration have been carried out to overcome the obstacles of intracellular transport of apoptotic proteins such as cytochrome, herceptin, apoptin, and ricin. These nanosystems for intracellular delivery of apoptotic proteins show longer plasma half-life, better cell selectivity, and superior anti-tumor ability.
[0004] Nanocarriers are a promising tool for in vitro targeting of drugs to solid tumors, which can achieve more stable and long-lasting formulations. Nanomedicine has become a popular field due to its advantages such as small size, low drug toxicity, sustained drug release, and convenient biodistribution. Nanocarrier systems combine nanotechnology with drug delivery systems and have many advantages over traditional tumor chemotherapy. First, the active ingredients of the drug are tightly wrapped or dispersed in the polymer material of the micro-nanocarrier, which improves the stability of the drug molecules during production, transportation, storage, and administration. After administration, as the shell material collapses and decomposes, the core material is gradually released slowly, and the drug effect is more lasting. The size of the nanocarrier is conducive to the cell's uptake of it by endocytosis, further prolonging the effective time of the drug's action, thereby enhancing the therapeutic effect. In addition to anticancer drugs, micro-nanocarriers can also encapsulate ultrasound or fluorescent contrast agents to achieve integrated diagnosis and treatment of patients; we can also add excitable medium materials to the carrier to control the time and space of drug delivery; nanocarriers can also be combined with biological targeting materials to improve the specificity of drugs to lesions. Compared with traditional medicines, medicines with excellent stability, sustained release, effectiveness and targeting can reduce the dosage of original medicines, which naturally reduces toxic side effects and drug costs. Summary of the invention
[0005] The present invention provides a novel method for preparing a UV-crosslinked nanogel carrier to address the limitations of protein therapy in cancer treatment, such as the inability to target release, short inactivation time, and poor membrane permeability. This novel nanogel carrier is crosslinked by UV light and uses cytochrome C for protein therapy, and has good biosafety and high anti-tumor efficiency. The novel UV-crosslinked nanogel carrier has the following characteristics: Lysosomal escape ability: Generally, nanoparticles enter cells through endocytosis and are degraded through the lysosomal transport pathway, thus losing their original function. In order to prevent this phenomenon, the nanogel was successfully grafted with diethylenetriamine to avoid being degraded by lysosomes and successfully escape into the cytoplasm.
[0006] Blood circulation and targeting: The presence of methoxypolyethylene glycol amino groups can prolong the circulation time of nanogels in the blood and reduce the adsorption of blood proteins, thereby improving their targeting.
[0007] Drug delivery and release: Hyaluronic acid, as the skeleton of the shell polymer, can target the CD44 receptor on the surface of tumor cells and enhance the endocytosis of the nanoparticles by tumor cells. Cytochrome C, as the active ingredient in the carrier, can achieve targeted drug release after reaching the tumor cells due to the particularity of the tumor microenvironment (such as low pH, high reducibility, etc.).
[0008] Responsiveness: Due to the presence of cystamine disulfide bonds, these nanogels have excellent tumor microenvironment responsiveness. After contacting tumor cells and being affected by the tumor microenvironment, the nanogels will quickly degrade and release protein therapeutic drugs.
[0009] In order to achieve the above requirements, the present invention adopts the following technical scheme, and the steps of the novel method for preparing ultraviolet cross-linked nanogel carrier are as follows: A. Synthesis process of polymer ligand 1: (1) Hyaluronic acid (HA), 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS) are dissolved in 15-30 mL of deionized water, wherein the molar amounts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are the same, and the molar ratio of HA to either of the two can be 1:1.2-1.4. The concentration range of EDC and NHS in the deionized water solvent is 0.5-3 mg / mL. The reaction is carried out at 30°C in a nitrogen atmosphere for 2 h to activate HA.
[0010] (2) Dissolve 1-2 g of methoxypolyethylene glycol amino (average molecular weight 5000) (mPEG) in 10-20 mL of deionized water, add the mixture dropwise to step (1), and react in a nitrogen atmosphere at 30° C. for 24-48 h to obtain PEGylated hyaluronic acid.
[0011] (3) The solution obtained in (2) is added dropwise into a 10 mL deionized water solution containing diethylenetriamine using a syringe pump, and the mixture is reacted in a nitrogen atmosphere at 30°C for 24 to 48 hours. After the reaction, the reaction solution is placed in a dialysis membrane with a molecular weight cutoff of 3000 to 8000, and dialyzed with a 0.01 to 0.05 mol / L hydrochloric acid solution for 24 to 48 hours. The mixture is then dialyzed with an excess of deionized water for two to three days, and freeze-dried to obtain a sodium hyaluronate polymer modified with methoxypolyethylene glycol amino and diethylenetriamine (HA-g-mPEG / Deta).
[0012] (4) Dissolve 0.15-0.20 g lipoic acid (DL-α-Lipoic Acid) and 0.13-0.15 g CDI (N,N'-carbonyldiimidazole) in 10-15 mL DMSO and react in a nitrogen atmosphere at 30°C for 2 h.
[0013] (5) Take 0.8-1.0 g of the polymer from (3) and add it to 15 mL of deionized water to dissolve it. After dissolution, use a syringe pump to inject it into the two-necked flask in (4). React in a nitrogen protection environment at 30°C for 24-48 h, place it in a dialysis membrane with a molecular weight cutoff of 3000-8000, and then dialyze it with excess deionized water for 48 h. Finally, freeze-dry it to obtain the polymer ligand (HA-g-mPEG / Deta-c-LA).
[0014] B. Preparation of nanogels and protein loading: (6) Weigh 100 mg of the polymer HA-g-mPEG / Deta-c-LA into a flask, dissolve it in 10–20 mL of deionized water, and irradiate it with 365 nm ultraviolet light for a certain period of time in the dark to allow it to crosslink and form a nanogel.
[0015] (7) Take 100 mg of Nanogel@LA and Cy5-labeled cytochrome C (Cy5-CC) in a flask, dissolve it in 10-20 mL PBS buffer solution, and irradiate it with 365 nm ultraviolet light for different reaction times in the dark, so that it can load cytochrome C under ultraviolet light irradiation (loading while irradiating). After irradiation, place the solution in a dialysis membrane with a molecular weight cutoff of 30,000, dialyze and purify it with excess deionized water (pH 7-8) for 20-24 h, and freeze-dry to obtain nanogel loaded with cytochrome C.
[0016] 2. The average molecular weight of the hyaluronic acid in the polymer 1 described in step (1) can be 7000-10000.
[0017] 3. The molar ratio of HA to EDC / NHS in the polymer 1 of step (1) is 1:1.2 4. The average molecular weight of the methoxypolyethylene glycol amino group (mPEG) in the polymer 1 described in step (2) is in the range of 2000 to 5000.
[0018] 5. The number of methoxypolyethylene glycol amino groups (mPEG) grafted to the hyaluronic acid (HA) main chain in the polymer 1 described in step (2) is 1 to 4.
[0019] 6. The molar ratio of diethylenetriamine (Deta) to repeating units of hyaluronic acid (HA) in the polymer 1 of step (3) is 20 to 40 times in excess, and the number of ligands of diethylenetriamine grafted hyaluronic acid is 15 to 25.
[0020] 7. The protein drug in the polymer 1 in step (7) can be cytochrome C, Granzyme B, Grb-2, etc.
[0021] 8. The pH range of the solution of the protein drug loaded by the nanogel in the polymer 1 described in step (7) is 7.4-8.0.
[0022] 9. The mass ratio of the polymer ligand to the protein drug in the polymer 1 described in step (7) is controlled in the range of 10:1 to 20:1.
[0023] The raw material containing a disulfide bond structure used in the method of the present invention may be DL-α-lipoic acid (DL-α-Lipoic Acid).
[0024] The protein therapeutic drugs used in the method of the present invention can be cytochrome C, Granzyme B and Grb- The method of the invention is to synthesize polymers in a pH 7.4-8.0 aqueous solution or PBS buffer solution, and under the irradiation of ultraviolet light, disulfide bonds are broken to form biradicals for cross-linking to form nanogels and load protein drugs.
[0025] Compared with the current technology, the present invention has the following advantages: The present invention provides a novel nanogel carrier formed by ultraviolet cross-linking to better treat cancer with proteins. Hyaluronic acid containing CD44 receptors targeting the surface of cancer cells is selected as the skeleton of the nanogel, which makes the positioning more precise and improves the treatment effect.
[0026] The hyaluronic acid backbone is grafted and modified. The methoxypolyethylene glycol amino group can prolong its circulation time in the blood system, the grafted diethylenetriamine can help lysosome escape, and the disulfide bonds in the gel can be destroyed by the high concentration of glutathione in the tumor microenvironment, causing the disintegration of the nanogel and releasing cytochrome C. That is, the characteristics of the tumor microenvironment are used to improve the efficiency of targeted release of proteins, and the control is more precise and flexible.
[0027] The prepared nanogel has good stability and biocompatibility in a variety of biological media.
[0028] Protein therapy is widely used in cancer treatment based on the advantages of protein drugs such as high therapeutic efficiency and low toxic side effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the synthesis route of the polymer ligand (HA-g-mPEG / Deta-c-LA) in Example 1.
[0030] Figure 2 This is the H NMR spectrum of hyaluronic acid grafted with polyethylene glycol and diethylenetriamine in Example 1; each group characteristic peak marked in the figure proves that the grafting of hyaluronic acid with polyethylene glycol and diethylenetriamine is successful.
[0031] Figure 3 This is the hydrogen nuclear magnetic spectrum of the final polymer in Example 1; each group characteristic peak marked in the figure proves that the polymer was successfully synthesized.
[0032] Figure 4 Schematic diagram of protein delivery by tumor microenvironment responsive nanogel in Example 1; the polymer undergoes ring-opening polymerization (ROP) under ultraviolet radiation (λmax = 365 nm) to form an independent nanogel. The strained disulfide bonds can be cleaved into diradicals by long-wavelength ultraviolet rays, thereby triggering the free radical polymerization of lipoic acid, and loading cytochrome C under ultraviolet light irradiation (loading while irradiating).
[0033] Figure 5 This is a transmission electron microscopy image of the nanogel loaded with cytochrome C in Example 1; the concentration is 1.5 mg / mL, and the scale bar in the legend is 100 nm.
[0034] Figure 6 The biological stability of nanogels in different biological culture media (1640, PBS).
[0035] Figure 7 The figure shows the potential comparison of nanogel under UV light irradiation for different time periods. As the illumination time increases, after photo-crosslinking, it becomes nanogel, and more positively charged groups are exposed, resulting in an increase in potential.
[0036] Figure 8 The Zeta surface potential diagrams of the nanogel before and after CC loading in Example 1 are compared; after CC loading, the potential of the nanogel decreases.
[0037] Fig. 9 The process of releasing cytochrome C from nanogels under the action of glutathione (GSH) over time was compared with the drug release from nanogels without glutathione, proving that the nanogels can be effectively decomposed by glutathione and release drugs.
[0038] Fig.10 Confocal images and 2.5D images of A549 and HepG2 cells incubated with Cy5-CC loaded nanogels for 4 hours, and A549 incubated with Cy5-CC alone for 4 hours. It was demonstrated that CD44 positive A549 cells were able to better take up CC loaded nanogels.
[0039] Fig.11Calcein-AM / PI staining was used to directly observe the killing effects of Free CC, Nanogel@LA, and Nanogel@LA / CC on A549 cells and HepG2 cells. Green fluorescence indicates live cells, and red fluorescence indicates dead cells. After 4 h of incubation, the number of dead cells increased. This indicates that Nanogel@LA / CC has killing effect on A549 cells and promotes the death of A549 cells.
[0040] Fig.12 The cell viability of A549 cells after being treated with different concentrations of CC, Nanogel@LA, and Nanogel@LA / CC in Example 1. It can be seen from the figure that the nanogel loaded with CC has the strongest killing ability against cancer cells and the best effect. DETAILED DESCRIPTION Example
[0041] The invention is described in detail below with reference to the accompanying drawings and specific embodiments. Specific embodiments
[0042] 1 g of hyaluronic acid (sodium hyaluronate) (average molecular weight 9100), 0.532 g of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 0.320 g of N-hydroxysuccinimide (NHS) were placed in a two-necked flask with a magnetic stirring rotor, 15 mL of deionized water was added to completely dissolve the drugs, and the mixed solution was reacted in a nitrogen protection environment at 30°C for 2 h. Subsequently, 1.099 g of methoxypolyethylene glycol amino (average molecular weight 5000) was added to the above solution, and the reaction continued in a nitrogen protection environment for 24 h. After that, the obtained hyaluronic acid and methoxypolyethylene glycol amino mixed solution was dripped into 15 mL of deionized water solution containing diethylenetriamine (7.45 mL) by a syringe pump, and reacted in a nitrogen protection environment at 30°C for 24 h. Then, it was placed in a dialysis membrane with a molecular weight cutoff of 7000 and dialyzed with 0.01 mol / L hydrochloric acid solution for 24 h, and then dialyzed with excess deionized water for 48 h and freeze-dried to obtain a solid powder of sodium hyaluronate modified with methoxypolyethylene glycol amino group and diethylenetriamine (HA-g-mPEG / Deta). 0.16 g of lipoic acid (DL-α-Lipoic Acid) and 0.14 g of CDI (N, N'-carbonyldiimidazole) were placed together in a two-necked flask with a magnetic stirring rotor, 10 mL of DMSO was added to completely dissolve the drug, and the mixed solution was reacted in a nitrogen protection environment at 30°C for 2 h. 0.8 g of sodium hyaluronate solid powder modified with methoxypolyethylene glycol amino and diethylenetriamine (HA-g-mPEG / Deta) was taken and dissolved in 15 mL of distilled water. After the dissolution was completed, it was injected into the two-necked flask containing lipoic acid and N, N'-carbonyldiimidazole with a syringe pump, reacted in a nitrogen protection environment at 30°C for 48 h, placed in a dialysis membrane with a molecular weight cutoff of 7500, and then dialyzed and purified with excess deionized water for 48 h, freeze-dried, and solid powder (HA-g-mPEG / Deta-c-LA).
[0043] Weigh 100 mg of polymer (HA-g-mPEG / Deta-c-LA) in a flask, dissolve it in 15 mL of deionized water, and irradiate it with 365 nm ultraviolet light for a certain period of time in the dark to cause photocrosslinking to form nanogel.
[0044] 100 mg of empty gel (HA-g-mPEG / Deta-c-LA) and Cy5-labeled cytochrome C (the total mass ratio of the first two polymers was 1:10) were taken into a flask, dissolved with 16 mL of PBS buffer solution, and irradiated with 365 nm ultraviolet light for 2 h in the dark to load cytochrome C under ultraviolet light irradiation. After irradiation, the solution was placed in a dialysis membrane with a molecular weight cutoff of 30,000, dialyzed and purified with excess deionized water (pH 7-8) for 24 h, and freeze-dried to obtain a nanogel loaded with cytochrome C.
[0045] The morphology of the prepared environmentally responsive nanoreagents is shown in Figure 5 As shown in the figure, through high-definition transmission electron microscopy, it can be seen that the particle size of the obtained nano-diagnosis and treatment integrated reagent is very small, with an average size of about 153 nm. The Zeta potential of the diagnosis and treatment integrated reagent was obtained by Malvern particle size analyzer at around -10 mV.
Claims
1. A novel ultraviolet cross-linked nanogel carrier, the preparation method of which comprises the following steps: A. Synthesis process of polymer ligand 1: (1) Dissolve hyaluronic acid (HA), 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS) in 15-30 mL of deionized water, wherein the molar amounts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are the same, and the molar ratio of hyaluronic acid to either of the two can be 1:1.2-1.
4. The concentration range of EDC and NHS in the deionized water solvent is 0.5-3 mg / mL. React in a nitrogen atmosphere at 30°C for 2 h to activate HA; (2) dissolving 1-2 g of methoxy polyethylene glycol amino (average molecular weight 5000) (mPEG) in 10-20 mL of deionized water and then adding the mixture dropwise to step (1), reacting the mixture in a nitrogen atmosphere at 30° C. for 24-48 h to obtain PEGylated hyaluronic acid; (3) The solution obtained in (2) was added dropwise into a 10 mL deionized water solution containing diethylenetriamine using a syringe pump, and the mixture was reacted in a nitrogen atmosphere at 30° C. for 24 to 48 hours. After the reaction, the reaction solution was placed in a dialysis membrane with a molecular weight cutoff of 3000 to 8000, and dialyzed with a 0.01 to 0.05 mol / L hydrochloric acid solution for 24 to 48 hours. The mixture was then dialyzed with excess deionized water for two to three days, and freeze-dried to obtain a sodium hyaluronate polymer modified with methoxypolyethylene glycol amino (mPEG) and diethylenetriamine (Deta) (HA-g-mPEG / Deta); (4) Dissolve 0.15-0.20 g lipoic acid (DL-α-Lipoic Acid) (LA) and 0.13-0.15 g CDI (N,N'-carbonyldiimidazole) in 10-15 mL DMSO and react in a nitrogen atmosphere at 30 °C for 2 h. (5) Take 0.8-1.0 g of the polymer from (3) and add 15 mL of deionized water to dissolve it. After dissolution, inject it into the two-necked flask in (4) using a syringe pump, react in a nitrogen atmosphere at 30°C for 24-48 h, place it in a dialysis membrane with a molecular weight cutoff of 3000-8000, then dialyze and purify it with excess deionized water for 48 h, and freeze-dry it to finally obtain the polymer ligand (HA-g-mPEG / Deta-c-LA); B. Preparation of nanogels and protein loading: (6) Weigh 100 mg of the polymer HA-g-mPEG / Deta-c-LA into a flask, dissolve it in 10-20 mL of deionized water, and irradiate it with 365 nm ultraviolet light for a certain period of time in the dark to cross-link it to form a nanogel (Nanogel@LA); (7) Take 100 mg of Nanogel (Nanogel@LA) and Cy5-labeled cytochrome C (Cy5-CC) in a flask, dissolve it with 10-20 mL PBS buffer solution, and irradiate it with 365 nm ultraviolet light for 10-12 h in the dark, so that it can load cytochrome C under ultraviolet light irradiation (loading while irradiating). After irradiation, place the solution in a dialysis membrane with a molecular weight cutoff of 30,000, dialyze and purify it with excess deionized water (pH 7-8) for 20-24 h, and freeze-dry to obtain a nanogel loaded with cytochrome C; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1 is characterized in that: The average molecular weight of the hyaluronic acid in step (1) may be 7000-10000; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1 is characterized in that: The molar ratio of HA to EDC / NHS in step (1) is 1:1.2; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1, characterized in that: the average molecular weight of the methoxypolyethylene glycol amino (mPEG) in step (2) is in the range of 2000 to 5000; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1, wherein the polymer is characterized in that: in step (2), the number of methoxypolyethylene glycol amino groups (mPEG) grafted to the hyaluronic acid (HA) main chain is 1 to 4; According to the method for preparing a novel UV-crosslinked nanogel carrier according to claim 1, the polymer is characterized in that: The molar ratio of diethylenetriamine to the repeating unit of hyaluronic acid (HA) in step (3) is 20 to 40 times in excess, and the number of ligands of diethylenetriamine grafted hyaluronic acid is 15 to 25; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1 is characterized in that: The illumination time in step (6) is controlled within a range of 0.5-12 hours; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1 is characterized in that: The protein drug in step (7) can be cytochrome C, Granzyme B, Grb-2, etc.; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1 is characterized in that: The pH range of the solution of the nanogel loaded with protein drug in step (7) is 7.4-8.0; The method for preparing a novel UV-crosslinked nanogel carrier according to claim 1, characterized in that the mass ratio of the polymer ligand to the protein drug in step (7) is controlled within a range of 10:1 to 20:1.
